In vitro reactivation of sarin-inhibited brain acetylcholinesterase from different species by various oximes - Kuca, K; Cabal, J; Kassa, J (Journal of enzyme inhibition and medicinal chemistry, 2005)
In vitro as well as in vivo evaluation of the reactivating efficacy of various oximes against nerve agent-inhibited acetylcholinesterase has been usually done with the help of animal experiments. Nevertheless, previously published data indicate that the reactivation potency of oximes may be different in human and animal species, which may hamper the extrapolation of animal data to human data. Therefore, to better evaluate the efficacy of various oximes (pralidoxime, obidoxime, HI-6, K033) to reactivate brain acetylcholinesterase inhibited by sarin by in vitro methods, human, rat and pig brain acetylcholinesterase were used to calculate kinetic parameters for the reactivation. Our results show differences among the species, depending on the type of oxime, and indicate that data from animal experiments needs to be carefully evaluated before extrapolation to humans.
Keywords: prasata; Swine; Cholinesterase Inhibitors; druhová specificita; pralidoximové sloučeniny; Obidoxime Chloride; Structure-Activity Relationship; Brain; Pralidoxime Compounds; Oximes; Species Specificity; sarin; acetylcholinesterasa; Cholinesterase Reactivators; Pyridinium Compounds; vztahy mezi strukturou a aktivitou; obidoxim chlorid; krysa rodu Rattus; kinetika; Animals; pyridinové sloučeniny; lidé; Humans; zvířata; Rats; reaktivátory cholinesterasy; mozek; oximy; Sarin; Acetylcholinesterase; cholinesterasové inhibitory; Kinetics